Innovative Transformation of New Technology-Based Firms: A Multiple-Case Study in Poland - Adam CZARNOTA; Joanna DYCZKOWSKA; Marcin OLKIEWICZ (Communications of International Proceedings, 2025)
The aim of this article is to analyse the transformation of the innovation activities of young technology firms during the COVID-19 pandemic. The study was empirical in nature. The research method is a multiple-case study based on three polish firms in Western Pomerania. The main source of data in the study was questionnaire which consisted of open and closed questions. The survey found that companies in order to survive the difficult entrepreneurial phase need to grow, hire qualified staff, internationalize and develop new products in a short time horizon.
Keywords: transformation; innovation; technology-based entrepreneurship; new technology-based firm